MENAKAR TRADISI KAWIN PAKSA DI MADURA DENGAN BAROMETER HAM - Sa’dan, Masthuriyah (Musawa Jurnal Studi Gender dan Islam, 2015)
There is a tradition of forced marriage (kawin/nikah paksa) in Madurese society in which young  females are paired up with and married off to young males of their parents choosing. Young women may be promised in marriage when they are still in their mothers’ wombs or in childhood, and the marriage age for girls is generally under the age of 18 years, though there are those who marry between 12-15 years. Regeneration of the ancestral lineage can be seen in several areas in Madura including Bangkalan, Sampang, Pamekasan and Sumenep. Instead of the following the prescriptions of Muhammad, girl children have become ‘victims’ of a culture that discriminates  against them. If seen from a human rights perspective, the tradition of kawin paksa breaches the ethics related to humanity, justice and equality.